OP54 Delivering system-wide advance care planning support in real-world settings: economic considerations. An exploratory, qualitative study in twelve international healthcare organisations. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Dixon, J; Knapp, M
Abstract : Background: Facilitation of ACP conversations is time consuming, whether undertaken in one or multiple shorter discussions. Our exploratory, qualitative study in twelve healthcare systems (US, Canada, New Zealand, Australia) providing system-wide ACP support explored: organizational rationales for provision, including perspectives on the economic case type and organization of staffing ways of providing high–quality, system–wide support cost–efficiently. Methods: Interviews with leaders, ACP specialists, physicians, nurses, social workers and others (average n=13) were conducted in twelve purposively-sampled healthcare systems. Data were transcribed and thematically analysed using NVivo software. Results: System-wide ACP support was primarily a strategic response to risks associated with increased availability and use of life-prolonging interventions in serious illness and frailty. Overall cost-savings were not expected. Staffing ACP support was challenging. While professionals often needed more protected time, promising approaches included team-based provision, especially physicians working with nurses and social workers, and systematic incorporation into chronic and routine care. Skilled and experienced staff underpinned cost-effective provision. While dedicated facilitators were not scalable or sustainable, some level of specialism and voluntarism, with plentiful opportunities to develop skills in practice, was indicated. ACP support was provided equally efficiently by experienced staff regardless of guides or approach used. Serious illness conversations could build on earlier ACP support. Community- and group-based approaches were thought cost-efficient, increasing reach and supporting later planning and decision-making. Conclusions: Investments in ACP support were justified by management of organizational risk and high-quality patient care. Our findings identify areas where cost-efficiencies in provision of system-wide ACP support may be found